Whoops! But it wasn't me - Child, Lauren (New York : Grosset & Dunlap, 2006)
Lola disobeys her brother Charlie and breaks the rocket that he just made, and then she must decide whether or not to tell him the truth about what happened.
Text based on script written by Bridget Hurst and Carol Noble.
2.7
K-3
Keywords: Brothers and sisters -- Fiction; Honesty -- Fiction; Imaginary playmates -- Fiction; Honesty -- Fiction; Imaginary playmates -- Fiction; Siblings -- Fiction